Oxidized LDL promotes EMS-induced angiogenesis by increasing VEGF-A expression and secretion by endometrial cells - Caiqi Ma; Wei Huang; Hui Wang; Wenxia Yao; Min Liang; Guifang Yu; Xinke Zhou (BMC, 2022)
Abstract Background Endometriosis (EMS) is a "tumour-like" gynaecological disease with distant metastasis, and studies have shown that EMS can induce distant metastasis through vascular vessels, but the driving factors and their mechanism are not clear. Methods We used an EMS animal model and gene knockout technique to explore the role of EMS-induced angiogenesis in EMS metastasis in vivo and in vitro and clarify the role and molecular mechanism of oxLDL in promoting EMS-induced angiogenesis. Results We found that microvascular density (MVD) in metastasized ectopic endometrium and eutopic endometrial tissue was higher than that in normal endometrial tissue, and plasma oxLDL was positively correlated with the distant metastasis of EMS. Furthermore, we clarified that oxLDL enhanced the MVD of endometrial tissue by increasing VEGF-A expression and secretion in endometrial cells. Finally, we illustrated the mechanism by which oxLDL promotes VEGF-A expression through the AKT-HIF-1α signalling pathway. Conclusion OxLDL is a risk factor promoting distant EMS metastasis by increasing VEGF-A expression and secretion through AKT-HIF-1α signalling. This finding may provide theoretical support and therapeutic targets for the clinical prevention and treatment of EMS.